Chloroplast membrane lipid remodeling protects against dehydration by limiting membrane fusion and distortion. Issue 1 (3rd November 2021) - Chng, Choon-Peng; Wang, Kun; Ma, Wei; Hsia, K Jimmy; Huang, Changjin
Abstract: Dehydration damages the structural integrity of the chloroplast membrane and, consequently, the normal photosynthetic function of this organelle. Remodeling of galactolipids by converting monogalactosyl–diacylglycerol (MGDG) to digalactosyl-diacylglycerol (DGDG) and oligo-galactolipids is an effective adaptation strategy for protecting against dehydration damage to the chloroplast membrane. However, detailed molecular mechanisms are missing. In this study, by performing molecular-level simulations of bi-lamellar membranes under various dehydration conditions, we find that MGDG-to-DGDG remodeling protects the chloroplast membrane in a unique manner by simultaneously dictating both the extent and the pattern of fusion stalks formed with the apposed membrane. Specifically, MGDG-rich membranes form elongated stalks at a moderate dehydration level, whereas DGDG-rich membranes form smaller, rounded stalks. Simulations of wild-type and mutant Arabidopsis ( Arabidopsis thaliana ) outer chloroplast membranes further confirm that the mutant membrane without galactolipid remodeling is more susceptible to membrane fusion due to its higher MGDG content. Our work reveals the underlying physical mechanisms that govern the pattern and extent of membrane fusion structures, paving the way for rational genetic engineering of crops with improved dehydration tolerance. Abstract : Galactolipid remodeling in chloroplast membranes alters both the extent and pattern of membrane fusion stalks to protect against cellular damage in response to dehydration.